Entrepreneurial orientation and SME international performance: The mediating role of networking capability and experiential learning. (March 2019) - Karami, Masoud; Tang, Jintong
This article extends knowledge of entrepreneurial orientation (EO) by examining EO in the context of international performance of small- and medium-sized enterprises (SMEs). We enhance understanding of foreign market entry of SMEs by taking into account the mediating mechanisms (i.e. networking capability and experiential learning) through which firm EO leads to superior performance across borders. A sample of 164 internationalising SMEs in New Zealand supported the direct impact of EO on international performance as well as the mediating role of experiential learning and networking capability in this focal relationship. These findings reveal the importance of EO in internationalisation of SMEs.